Determinants of Wholly Owned Foreign Direct Investments in E-Commerce Firms: A Hierarchical Country- and Firm-Level Analysis - Marius Mueller; Bernhard Swoboda (Management International Review, 2025)
Despite their digital nature, leading and globally expanding e-commerce firms establish a physical presence in select countries over time to implement full local operations and management. However, we know surprisingly little about the drivers of such wholly owned foreign direct investment decisions in certain countries, while other countries are served virtually. This study proposes a framework for the specific, business model-related firm- and host-country antecedents of e-commerce firms' wholly owned foreign direct investment. We employ novel data concerning 1,726 operation modes chosen by the 241 leading e-commerce firms in Europe from 2010–2020 and apply multilevel modeling. In contrast to manufacturing firms, the insights reveal how e-commerce firms leverage previously unknown online experience capabilities to inform foreign direct investment decisions, challenging the currently questioned role of experience in international business research on digital firms. Moreover, business model-related country-level antecedents, such as host country logistics performance, the internet user population, or the rule of law, also explain such decisions differently. These findings contribute to the emerging research on digital firms' internationalization and have direct implications for e-commerce managers interested in the drivers of foreign direct investment but also for manufacturers. The latter increasingly use e-commerce firms for their own international expansion, whereas policymakers aim to attract growing e-commerce firms to establish their own presence in host countries.
Keywords: 330; E-commerce firms; Foreign direct investment; Logistics performance; Internet use; Rule of law; International online experience; Multilevel modeling